Pelatihan Branding dan Komunikasi Visual bagi Siswa SMK Al-Islah Surabaya - Reizano Amri Rasyid; Mohammad Yusak Anshori; Azmil Chusnaini; Akhmad `Izzul `Arobi (Abimanyu : Jornal of Community Engagement, 2026)
This community service activity was initiated to respond to the gap between the technical capabilities and strategic understanding of advertising among vocational high school (SMK) students in the field of Visual Communication Design (DKV). The purpose of this program is to improve students’ understanding of advertising as a strategic communication tool that involves branding, message construction, and audience targeting. The method used consisted of four stages: needs analysis, program planning, training implementation, and evaluation. The activity involved 40 students and was carried out through interactive, practice-based sessions over two days. The results showed a significant improvement in students’ comprehension of advertising strategies, brand identity, and visual communication. Students also demonstrated growth in soft skills such as public speaking, collaboration, and creative thinking. The overall outcome indicates that this training model is effective in enhancing both conceptual understanding and practical competence relevant to the creative industry